2007
DOI: 10.3200/jach.56.2.159-164
|View full text |Cite
|
Sign up to set email alerts
|

HPV Knowledge and Behaviors of Black College Students at a Historically Black University

Abstract: Findings suggest a greater need for HPV intervention efforts for all college students, including those at black colleges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 11 publications
3
29
1
2
Order By: Relevance
“…They had rather low levels of awareness and information about HPV. Although previous studies reported that students had high levels of knowledge about HPV and increasing levels of awareness, 33 in parallel to our findings, levels of knowledge and awareness regarding HPV 1,13,35,37,[44][45][46][47]53,54 were low and they did not consider themselves at risk for HPV infection. 37 Students' sources of information on HPV were newspaper/magazines, television/radio, the Internet, and books (11.7%, 8.1%, 6.4%, and 4.5%, respectively).…”
Section: Resultscontrasting
confidence: 54%
“…They had rather low levels of awareness and information about HPV. Although previous studies reported that students had high levels of knowledge about HPV and increasing levels of awareness, 33 in parallel to our findings, levels of knowledge and awareness regarding HPV 1,13,35,37,[44][45][46][47]53,54 were low and they did not consider themselves at risk for HPV infection. 37 Students' sources of information on HPV were newspaper/magazines, television/radio, the Internet, and books (11.7%, 8.1%, 6.4%, and 4.5%, respectively).…”
Section: Resultscontrasting
confidence: 54%
“…Although most participants reported having heard of HPV and the vaccine, preintervention HPV knowledge was modest, which is consistent with the literature. 42,43 The low levels of knowledge preintervention emphasize the need for educational interventions among young adults. Males had lower levels of knowledge than females preintervention, which is also consistent with the literature.…”
Section: Commentmentioning
confidence: 98%
“…Many studies have focused on parental willingness to vaccinate their children (Bair et al, 2008;Brabin et al, 2006;Chan et al, 2007;Dempsey et al, 2006;Dinh et al, 2007;Gerend et al, 2006;Lenselink et al, 2008;Marlow et al, 2007;Mays et al, 2004;Noakes et al, 2006;Ogilvie et al, 2007;Sperber et al, 2008;Woodhall et al, 2007). To a lesser extent, studies have examined vaccine knowledge, attitudes and intentions of young women (Crosby et al, 2007;D'Urso et al, 2007;Gerend et al, 2006;Gerend and Magloire, 2008). Recent reviews (Brewer and Fazekas, 2007;Klug et al, 2008;Zimet et al, 2006) show that among those who are aware of the relationship between HPV and cancer, acceptance of the vaccine is high.…”
Section: Introductionmentioning
confidence: 96%